Representações acerca de comportamentos (in) adequados: reflexões em um contexto de ensino de inglês na escola pública - Wada, Adriana Pavão (2014)
This study is a qualitative (DENZIN & LINCOLN, 2005) research and characterizes a case study research (CAMPORY, 2005; DUFF, 2008; JOHNSON, 1992; NUNAN, 1992; STAKE, 1995, 1998; YIN, 2005, 2009), which investigates in which extent the realization of teaching and learning English activities focusing on the theme behavior, can lead the students to reflect on their own behavior. To accomplish with its aim, it is based on theoretic studies about critically reflective teacher education (CELANI, 2002, 2003; DEWEY, 1933/1997; FREIRE, 1998; JOHNSON; FREEMAN, 2001; SMYTH, 1993; ZEICHNER, 1987); on studies about critical pedagogy (CANAGARAJAH, 2005; PENNYCOOK, 1990); on studies about representations (JODELET, 2008; MOSCOVICI, 1961/1978; 2000/2003); on the proposals contained in the official documents as Parâmetros Curriculares Nacionais de Língua Estrangeira (BRASIL, 1998) and Currículo do Estado de São Paulo para a Disciplina Língua Estrangeira Moderna (SÃO PAULO, 2010). This research was conducted in a public school located on a large city of São Paulo s district and its participants were seven students of the English language discipline and the teacher-researcher. Questionnaire, an audio recording of one class and teacher-researcher reflective diaries were the instruments through which all the data was collected. The results show that the representations of the teacher-researcher before and after the practice of the English activities and the representations of the students during the practice of the English activities focusing on the behavioral aspects influenced the reflection of the students about their attitudes, as evidenced in their behaviors in the classroom. Regarding to the teacher, this has undergone transformation no change in the way they perceive student behavior which characterizes the reflective process was ongoing